2009
DOI: 10.1093/jopart/mup027
|View full text |Cite
|
Sign up to set email alerts
|

Personnel Flexibility and Red Tape in Public and Nonprofit Organizations: Distinctions Due to Institutional and Political Accountability

Abstract: Academics and journalists have depicted government bureaucracies as particularly subject to administrative constraints, including the infamous red tape and personnel rules that sharply constrain pay, promotion and dismissal and weaken their relations to performance.Research on these topics has often focused on public organizations alone or on comparisons of public and private organizations. The analysis reported here extends this research to include nonprofit organizations. Certain theoretical perspectives wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 47 publications
1
65
0
9
Order By: Relevance
“…Empirical studies assessing the differences between public and nonprofit organizations are relatively sparse, creating gaps in our understanding about the implications these organizational differences have for managers. Although nonprofit and public organizations are similar in that they provide services in many of the same industries, pursue public-serving missions without providing financial gains to stockholders or individual owners, attract public service-minded individuals (Rotolo and Wilson 2006), and place greater importance on personal relations than private sector organizations (Rawls et al 1975), researchers have begun to investigate differences in management and work life across public and nonprofit organizations (Borzaga and Tortia 2006;Feeney and Rainey 2010;Rotolo and Wilson 2006). There is evidence that nonprofit workers report higher job commitment and satisfaction compared to public sector employees (Borzaga and Tortia 2006;Mirvis 1992;Mirvis and Hackett 1983).…”
Section: Differences In Nonprofit and Public Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies assessing the differences between public and nonprofit organizations are relatively sparse, creating gaps in our understanding about the implications these organizational differences have for managers. Although nonprofit and public organizations are similar in that they provide services in many of the same industries, pursue public-serving missions without providing financial gains to stockholders or individual owners, attract public service-minded individuals (Rotolo and Wilson 2006), and place greater importance on personal relations than private sector organizations (Rawls et al 1975), researchers have begun to investigate differences in management and work life across public and nonprofit organizations (Borzaga and Tortia 2006;Feeney and Rainey 2010;Rotolo and Wilson 2006). There is evidence that nonprofit workers report higher job commitment and satisfaction compared to public sector employees (Borzaga and Tortia 2006;Mirvis 1992;Mirvis and Hackett 1983).…”
Section: Differences In Nonprofit and Public Organizationsmentioning
confidence: 99%
“…choose nonprofit work settings over government, or vice versa (Feeney and Rainey 2010). Early studies that compare nonprofit employees to those in the for-profit and public sectors have found that nonprofit employees report more satisfaction with their jobs and have more trust in management than those in other sectors (Mirvis 1992;Mirvis and Hackett 1983).…”
mentioning
confidence: 99%
“…Несмотря на сложность и продуманность, теория управления имеет ряд существенных недостатков. На-пример, объясняя механизм применения клиентоори-ентированного подхода, Barzelay пишет: «В типичных клиентских отношениях пользователи считают, что поставщики должны быть подотчетны им (и, возмож-но, другим сторонам) в отношении [удовлетворения потребностей клиентов], и поставщики признают, что они должны быть в этом подотчетны» 165 . Эти рекомен-дации имеют смысл, однако термин «подотчетность» не определен и фактически скрывает критическую неопределенность [343, рр.…”
Section: администрирование ориентированное на кли-ента: управленчunclassified
“…Теоретически, и судя по нравственным проповедям чиновники должны быть подотчетны людям, которым законодательно должны служить. Однако из-за раз-личий в статусе, отношений с незнакомыми людьми, институциональных недостатков и дивергентных 165 [293, р. 110 стимулов они не являются подотчетными ни в каком смысле 167 .…”
Section: администрирование ориентированное на кли-ента: управленчunclassified
See 1 more Smart Citation